2007
DOI: 10.17221/2341-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weaning age on performance and nutrient digestibility of broiler rabbits

Abstract: AbstrAct:The effect of weaning age on growth, feed consumption, digestibility of nutrients, carcass yield, mortality and parasite incidence was studied in a balance experiment. Forty Hyplus ® rabbits proceeding from a commercial rabbitry were assigned to four groups of 10 rabbits according to weaning age at 25, 28, 31 and 35 days. The experimental diet had 17.03% crude protein, 4.66% fat and 18.30% crude fibre. Feed and water were available ad libitum. At the end of the experiment, at 84 days of age, six rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
7
10
0
3
Order By: Relevance
“…On the other hand, they were similar to those obtained by Volek and Marounek (2009) Coefficients of CP digestibility were similar to those obtained in studies by Tůmová et al, (2003), Zita et al, (2007), LakabiIoualitene et al, (2008), and . A higher level of protein digestibility, exceeding 80%, was noted in studies by Strychalski, Juśkiewicz et al (2014) and Gugołek et al (2015) in groups of animals characterized by higher productivity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, they were similar to those obtained by Volek and Marounek (2009) Coefficients of CP digestibility were similar to those obtained in studies by Tůmová et al, (2003), Zita et al, (2007), LakabiIoualitene et al, (2008), and . A higher level of protein digestibility, exceeding 80%, was noted in studies by Strychalski, Juśkiewicz et al (2014) and Gugołek et al (2015) in groups of animals characterized by higher productivity.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were achieved by Daszkiewicz et al (2012) in New Zealand White Rabbits, in an extensively fed group. In turn, as regards typical rabbits bred for meat, the slaughter yield calculated using this method is usually higher, and exceeds 50% (Zita et al 2007;Volek & Marounek 2009;Gugołek et al 2011;Strychalski, Juśkiewicz et al 2014;Gugołek et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Results of this study are similar to reports of Zita et al (2007) where they observed no significant (P>0.05) effect of weaning age and nutrient digestibility on the performance of broiler rabbits. Similarly, Xiccato et al (2000) did not also observe any significant influence of weaning age on the growth of rabbits, although Fortun-Lamothe et al (2002) had showed that early weaning provided higher viability and fastest growth in weaned rabbits.…”
Section: Body Weights and Weight Gainssupporting
confidence: 90%
“…Mortality has been reported to be affected by age at weaning (Zita et al, 2007). In this study, no mortality was recorded throughout the experimental period of fourteen weeks.…”
Section: Mortalitymentioning
confidence: 48%
See 1 more Smart Citation